2021
DOI: 10.3390/ijerph18136978
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Esthetic and Structural Aspects in Class II Functional Therapy. A Case–Control Retrospective Study

Abstract: To compare the skeletal, dental, and esthetic changes produced by three functional devices, Fränkel-2 appliance (FR-2), Twin Block (TB), and Occlus-o-Guide® (O-o-G®), for the treatment of Class II malocclusion. Methods: Sixty-five patients with Class II Division 1 malocclusion were divided into three groups and were analyzed through cephalometric analysis of skeletal, dental, and esthetic variables before and after treatment. The first group of 23 patients (F: 9; M: 14; mean age: 10.3 ± 1.08 years) was treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In a prospective study assessing soft tissue aesthetic changes, there was a significant reduction in facial convexity and upper lip protrusion following treatment with a modified Twin Block appliance [ 34 ]. A retrospective case–control study revealed that the aesthetic assessment yielded notably better outcomes in the Twin Block group, particularly in terms of diminishing facial convexity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study assessing soft tissue aesthetic changes, there was a significant reduction in facial convexity and upper lip protrusion following treatment with a modified Twin Block appliance [ 34 ]. A retrospective case–control study revealed that the aesthetic assessment yielded notably better outcomes in the Twin Block group, particularly in terms of diminishing facial convexity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different elastomeric appliances have been designed to treat many forms of malocclusions [ 38 ]. Generally, these devices feature two double-matched planes, upper and lower, and two flanges, one on the vestibular side and one on the lingual side.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a good alignment of the incisors was observed in 98% of the treated children. This alignment was possible because the eruption guidance appliance was designed to solve crowding by expanding the dental arches [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. It was concluded that the Fränkel group, the EGA group and the EGA subgroup had significantly greater resorption than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys have shown that the prevalence of Class II malocclusion among children in China varies slightly at each dental stage, ranging from 25.8% at early mixed dentition to 19.4% at early permanent dentition ( Minkui Fu et al, 2002 ). For the orthodontic treatment of patients with Class II malocclusion at Growth and development period (around puberty), early functional orthopedic treatments, such as Activator ( Oh et al, 2020 ), Herbst ( Souki et al, 2017 ; Wei et al, 2020 ), Frankel II ( Galluccio et al, 2021 ), and Twin block ( Uy-Co et al, 2010 ), are usually used to induce displacement of the mandibular condyle in the downward and forward directions to promote forward mandibular growth, reduce the facial shape of the Class II skeleton, and reduce the need for later surgery. However, there is still a lack of research on the mechanism through which tensile stress promotes the growth and development of condylar cartilage.…”
Section: Discussionmentioning
confidence: 99%